Realita Dinamika Pasar: Studi Intensif Distingsi Syariah Konvensional - Yadi Nurhayadi; Daram Heriansyah; Eva Susanti; Siti Azizziah Azzahra (Universitas Muhammadiyah Prof. DR. HAMKA, 2019)
The research confirm the differences between sharia company stock index and conventional company stock index as the issuer at The Indonesia Stock Exchange. This research is a continuation of a series of previous studies by Nurhayadi et al earlier on the comparison between the sharia market and the conventional market. The Data consist of Jakarta Stock Exchange (JSX) Composite Index (Indeks Harga Saham Gabungan (IHSG)), Jakarta Stock Exchange Liquid Index (LQ45), Jakarta Islamic Index (JII), Indonesia Sharia Stock Index (ISSI), ten companies of sharia issuer, and ten companies of conventional issuer. There are seven scenarios based on bivariate and multivariate analysis that conducted regression, correlation, and determination test to know whether conventional company influence on sharia company. The research scenarios cover five years data from January 2014 to December 2018. The result confirms that the fluctuation of conventional issuer's stocks is different from the fluctuation of sharia issuer's stocks. Conventional issuers have a weak correlation with sharia issuers. This condition implies that between the conventional market and the Islamic market there is no correlation.